Making Flowers Speak: Petrarch and Idiorrhythmy. (3rd July 2021) - Southerden, Francesca
ABSTRACT: This article brings Petrarch's (1304–74) lyric poetry into dialogue with Barthes's notion of "idiorrythmie" (idiorrhythmy) as outlined in his lecture course Comment vivre ensemble ( How to Live Together ). It explores both the idiorrhythmic aspects of Petrarchan desire and the traits of lyric utterance through which they are expressed, with a focus on canzone 126 of Petrarch's Rerum vulgarium fragmenta ( Fragments of Vernacular Things ). The article begins with a study of Barthes's exposition of idiorrhythmy: its medieval origins in the monastic communities of Mount Athos and the productively unstable and improvised character of the "living together, " and apart, that it implies. Most significant for the analysis that follows is idiorrhythmy's relationship to eros, Barthes's idea that idiorrhythmy preserves a space for the body's desires in opening to interruptions, deviations, and digressions. The remainder of the article offers a close reading of Petrarch's Rvf 126, focusing on one image in the poem that, like Barthes's idiorrhythmy, is rooted in fantasy and embraces errancy: the image of a flower that turning and falling around the poet's beloved seems to speak of love.